Soil legacy data rescue via GlobalSoilMap and other international and national initiatives. (December 2017) - Arrouays, Dominique; Leenaars, Johan G.B.; Richer-de-Forges, Anne C.; Adhikari, Kabindra; Ballabio, Cristiano; Greve, Mogens; Grundy, Mike; Guerrero, Eliseo; Hempel, Jon; Hengl, Tomislav; Heuvelink, Gerard; Batjes, Niels; et al.
Highlights: Soil legacy data are rescued in many parts of the world. Soil profiles data and soil maps are stored in harmonized databases. These data are capitalized upon using digital soil mapping techniques. High resolution maps of soil properties are produced according to GlobalSoilMap specifications. Abstract: Legacy soil data have been produced over 70 years in nearly all countries of the world. Unfortunately, data, information and knowledge are still currently fragmented and at risk of getting lost if they remain in a paper format. To process this legacy data into consistent, spatially explicit and continuous global soil information, data are being rescued and compiled into databases. Thousands of soil survey reports and maps have been scanned and made available online. The soil profile data reported by these data sources have been captured and compiled into databases. The total number of soil profiles rescued in the selected countries is about 800, 000. Currently, data for 117, 000 profiles are compiled and harmonized according to GlobalSoilMap specifications in a world level database (WoSIS). The results presented at the country level are likely to be an underestimate. The majority of soil data is still not rescued and this effort should be pursued. The data have been used to produce soil property maps. We discuss the pro and cons of top-down and bottom-up approaches to produce such maps and we stress their complementarity. We give examples of success stories. The first global soil property maps using rescued data were produced by a top-down approach and were released at a limited resolution of 1 km in 2014, followed by an update at a resolution of 250 m in 2017. By the end of 2020, we aim to deliver the first worldwide product that fully meets the GlobalSoilMap specifications.